Streamlining climate change, climate risk management in Agriculture, climate information services, and climate-smart agriculture innovations into undergraduate university curriculum modules in Ethiopia - Belay, Berhanu; Ambaw, Gebermedihin; Amha, Yosef; Makonnen, Brook T.; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Ethiopia, as is the case for other African countries, is a disproportionately higher risk of adverse consequences of climate change. The country has a high risk of hydrometeorological hazards and natural disasters. Its vulnerability is further exacerbated due to the high poverty level and its dependence on key sectors most likely affected by climate change: agriculture, water, tourism, and forestry. The country is considered a climate hotspot where climate change poses grave threats to human well-being and natural environments. The accelerating pace of climate change in the region is invariably being felt through increased extreme weather and variability, which affects the frequency, intensity, spatial distribution, duration and timing of severe weather and climate events. The changes in the frequency and severity of extreme climate events and the increasing variability of weather patterns result in substantial challenges for both human and natural systems. The major and almost exclusive livelihood activities of rural Ethiopia are crop production, livestock production, natural resource extraction, and only less than a small percentage engaged in off-farm activities.